(untitled) (Altre Modernità, 2025)
This paper seeks to analyze how Rovani’s figure and works circulated in the French press and among critics even in the absence of translations. Through quick allusions or more consistent studies, we see that between the 1850s and the present day, “something” filters out of the Milanese writer, from his activity as a music critic to his ability to portray Venice to his symbolic status as the leader of the bohème: through simplifications and truncated quotations, an image of a marginal writer emerges that is also functional to a reflection on what French culture chooses to promote or ignore in Italian literature.